Application of the value stream mapping concept in automotive sector - Silva, Rayner Vaz e; Nunes, Deivid Marques (Brazilian Journal of Production Engineering, 2023)
The Lean Manufacturing philosophy has been practiced in organizations with the aim of optimizing processes and reducing waste, increasing their performance and competitiveness against the competition. The philosophy has tools to be implemented in the organization, one of which is the Value Stream Mapping (MFV). In this way, the present study aims to map the value stream of the inspection process of a company in the automotive sector through the case study, identifying possible waste and proposing improvements. The experimental research carried out has a qualitative-quantitative approach, generating results that reaffirm the aim of the research. The methodological application of the MFV tool resulted in the elaboration of the mapping of the current state and later of the future state, after analyzes and improvements raised as reduction of rework, increase of operational load, elimination of stock and bottlenecks, which generate a high waste. The tool enabled the reduction of 87.68% in the lead time of the process, elimination of costs of 1 labor and the increase of 20.12% in the added value of the operation. The study carried out allowed expanding horizons of implementation of continuous lean production in existing gaps in the different sectors and scenarios of the company